Evaluasi dan Pengendalian Mutu Pembelajaran PAI Berbasis SPMI: Persespi Guru PAI dan Tim Mutu di SMP Khalifah Boarding School Sukabumi - Syarif Hidayatullah; Mulyawan Safwandy Nugraha (Jurnal Inovasi Pembelajaran dan Pendidikan, 2026)
This study aims to analyze the evaluation and quality control of PAI learning based on SPMI from the perspectives of teachers, principals, and students at SMP Khalifah Boarding School Sukabumi. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews with four purposively selected participants, consisting of one principal, one PAI teacher, and two ninth-grade students, and were analyzed thematically. The results indicate that learning planning has been systematically structured and aligned with national standards as well as the boarding school program. Quality control is carried out adaptively through the PDCA cycle and peer teaching practices, while assessment is conducted comprehensively, covering cognitive, affective, and psychomotor aspects, supported by journals and feedback mechanisms. However, several challenges remain, including the dominance of lecture-based methods and the limited implementation of student-centered learning. This study concludes that the implementation of SPMI has contributed to the development of a reflective and value-oriented quality culture. Nevertheless, strengthening pedagogical innovation and integrating active learning approaches are still needed to sustainably improve the quality of PAI learning.